Field Tests and Simplified Calculation Method for Static Drill Rooted Nodular Pile - Zhong-Jin Wang; Ri-Hong Zhang; Xin-Yu Xie; Peng-Fei Fang; Ling-Wei Zheng; Jin-Zhu Li; Da-Yong Zhu (Advances in Civil Engineering)
In order to explore bearing characteristics of a new-type static drill rooted nodular pile foundation (SDRN), which is composed of PHC pile, bamboo joint pile, and cement soils, field tests of three piles were carried out by embedding internal rebar stress gauges to collect test data. The test results show that the SDRN piles were under elastic state and the load-settlement curves changed slowly before reaching the ultimate capacity. As pile head loads increased, the pile shaft frictions developed progressively, and axial forces gradually reduced along pile depths. Taking into account the interaction between the pile, the cement soils, and surrounding soils, a simplified method for calculating settlements and bearing capacity of SDRN piles was proposed. With corresponding parameters, the computing results obtained by the proposed method were compared with the field experimental data, which indicates acceptable agreements; thus, it is concluded that the applicability and predictive capability of the proposed method were verified.